PENERAPAN INOVASI PELAYANAN ROBOT BOJONEGORO TANGGUH (BOBOTA) DI POLRES BOJONEGORO DALAM MENDUKUNG PROGRAM KAMPUNG TANGGUH SEMERU SEBAGAI UPAYA MENEKAN PENYEBARAN COVID-19 - Berliana Arta Migia Dwi Saharsa; Eva Hany Fanida (Publika, 2022)
The Covid-19 virus has become a global pandemic that has an impact on all aspects of the world, including Indonesia, including in Bojonegoro, so to tackle Covid-19 in Bojonegoro, the flagship program of the East Java Police, namely Kampung Tangguh Semeru, is to fight the spread of the Covid-19 virus, the Bojonegoro Police. has a service innovation program for the technology era during the pandemic which has six features in it, namely starting from the ALPR (Automatic License Plate Recognition) camera, AI Camera (FaceMask Detection Alert), video calls, Announcement Speaker, Mobile Traffic Light, PTZ Camera 270 degrees and Camera 360 degrees. The Bojonegoro Police service innovation program is the Bojonegoro Tough Robot (Bobota). The purpose of this study was to determine and analyze the implementation of the Bobota program innovation in supporting the Tangguh Semeru Village program by the Bojonegoro Police. The method used in this research is descriptive with a qualitative approach through the process of literature study, interviews, observation, and documentation. The focus of this research lies in the innovation of the Bojonegoro Police service in the application of the Bojonegoro Tangguh Robot (Bobota). The results of this study indicate that there are still shortcomings and problems, namely time efficiency. The Bobota service program is one of the innovations to assist the police in carrying out safe, modern and innovative patrol duties during the Covid-19 Pandemic in the jurisdiction of the Bojonegoro Police. Keywords: Covid-19, Service Innovation, Bobota.